Organic Wastewater Treatment using Two-dimensional Graphene-based Photocatalysts: A Review - Kelvert Kong; Zhiying Zhu; Mukhamad Nurhadi; Sumari Sumari; Siew Fan Wong; Sin Yuan Lai (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Photocatalysts have gained enormous attention in water decontamination due to their economic viable and intriguing properties. Recently, graphene-based semiconductors have become the sparkling star on the horizon of material science. The coupling of two-dimensional graphene and its derivatives (graphene oxide and reduced graphene oxide) with semiconductors could effectively enhance the efficiency in organic wastewater degradation under light irradiation. Hence, a collective study on this topic is necessary. Four types of graphene-based semiconductors, viz. titania, zinc oxide, cadmium sulfide, and bismuth oxychloride, are explored. Besides, synthesis approaches and properties of these photocatalysts are elucidated too. We hope this review could enable us to rationally design and harness the morphology, structure and electronic properties of these advanced materials. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).